“The era of the slaves is over”: Gender and work conditions in cleaning businesses in Argentina - Capogrossi, Lorena (2020)
This research emanates from a series of questions about the characteristics of the non-domestic work of women in cleaning businesses in Cordoba, Argentina. The problem is approached from a theoretical-methodological qualitative perspective that draws from ethnographic instruments. In this way observations, fieldwork reports, and semi-structured interviews with flexible questionnaires allowed for the gathering of a corpus of information that was systematized in this article. Two aspects were selected: on the one hand, the universe that surrounds the conditions of workers in the sector, including contracting, salaries, the types of tasks that they perform and the high turnover in places of employment; on the other hand, the analysis of some aspects of disciplining that takes place in these spaces. The analyzed dimensions make it possible to characterize the sector as an option that is preferable to other jobs, such as remunerated domestic work, because the relationship of dependency with these businesses grants a certain formality that did not exist before in most work trajectories of the interviewed women. Their work conditions, however, are constructed on a framework of violated rights and hierarchical relationships.